(untitled) (World Science, 2020)
The relationships between linear dimensions of the lumbar intervertebral discs (IVDL1-L2, IVDL2-L3, IVDL3-L4, IVDL4-L5) and somatometric parameters in girls and females of the first adulthood were investigated. The numerous relationships between the partial (height, sagittal and transverse sizes) linear dimensions and total sizes of the lumbar intervertebral discs in girls and women of the first adulthood (16-26 years) with their somatometric parameters were found. The linear dimensions of the lumbar intervertebral discs (height, sagittal and transverse sizes) were measured on the MRI images in the axial, sagittal and coronal plains. The arithmetic means of absolute correlation coefficients between particular and total individual sizes of IVDL1-L2, IVDL2-L3, IVDL3-L4, IVDL4-L5 and relative quantity with somatometric parameters were calculated with following results: arithmetic means of absolute correlation coefficients for particular individual sizes are within 0,120 - 0,170; for total sizes – 0,190; for ratio of the total sizes to the mass-growth coefficient – 0,507.